Bibliometric evaluation of agricultural literature published in Malaysia - Nasir, A.M.; Hassan, H.; A. Hamid, K.; Agha, S.S. (Kluwer Academic Publishers, 1994)
A bibliometric analysis of agricultural literature published in Malaysia between 1981-1990 was undertaken. The analysis shed light on the key journals that published agricultural literature; on the forms of publications which are resorted to in the communication of research results; on the subject areas which are well written on and those that have been neglected; on the nature of contributions made by Malaysian authors; on the publishing practice of corporate bodies and on the number of publications produced each year. © 1994 Akadémiai Kiadó.